(untitled) (Sustainability in Debate, 2010)
The representation of the environmental health concept in the realm of public policy, like the the web of conections balance expression is discuss in this work with the intention to demonstrate the status quo of environmental health in public policies in Brazil. First, was traced the history of the environmental notions influence on the concept of health, the history of the environmental health concept evolution and the institutionalisation both the environmental politics and health politics at Ministerial level. The interactions between politics of Ministry of Health and Ministry of Environmental to an effective National Policy of Environmental Health and intersections in the final results from The National Health Conference, The National Environmental Conference and The National Health Environmental Conference was analyzed, concluding with the advances obtained by the two sectors, the challenges to articulate an intersection between them and the social participation to the construction of the environmental health public policy.